A 0.5-V novel complementary current-reused CMOS LNA for 2.4 GHz medical application. (September 2016) - Dai, Ruofan; Zheng, Yunlong; He, Jun; Liu, Guojun; Kong, Weiran; Zou, Shichang
Abstract: A 0.5-V low noise amplifier (LNA) for 2.4 GHz medical application based on 0.18 μm CMOS process is presented in this paper. To achieve low noise and high gain with the constraint of low voltage and low power consumption, a novel modified complementary current-reused LNA using forward body bias technology is proposed. A diode connected MOSFET forward bias technique is employed to minimize the body leakage and improve the noise performance. A notch filter isolator with harmonic rejection is constructed to improve the linearity of low voltage. The measured results show that the proposed LNA achieves a power gain of 18.7 dB and a noise figure of 1.52 dB, while the consuming DC current is only 4.2 mA at supply voltage of 0.5 V.